Profile of Private Hospitals in the Philippines - Rouselle F. Lavado; Ida Marie T. Pantig; Valerie Gilbert T. Ulep; Maria Blesila G. Datu; Danica Aisa P. Ortiz; Jeanette F. Jimenez; Eduardo P. Banzon (Philippine Institute for Development Studies (PIDS), 2011)
As a recognition of the valuable role of private sector in the healthcare delivery system, this paper attempts to collate vital information on private hospitals in the Philippines. This paper looks at the different characteristics and structures of private hospitals sector with regard to geographical distribution, services, financing, human resource, and other information needed by policymakers, investors, and other interested stakeholders. To better understand the current health care delivery system in the country, other sections compare private hospitals vis-a-vis government-owned facilities.
Keywords: 330; health sector; health care; health facilities; hospitals; health care reform; health care financing; health management; private sector participation; Philippines; health; health care markets; private sector; health services delivery; Gesundheitsversorgung; Krankenhaus; Gesundheitsfinanzierung; Gesundheitsreform; Privatisierung; Philippinen